Characterizing and sourcing ambient PM2.5 over key emission regions in China I: Water-soluble ions and carbonaceous fractions. (June 2016) - Zhou, Jiabin; Xing, Zhenyu; Deng, Junjun; Du, Ke
Abstract: During the past decade, huge research resources have been devoted into studies of air pollution in China, which generated abundant datasets on emissions and pollution characterization. Due to the complex nature of air pollution as well as the limitations of each individual investigating approach, the published results were sometimes perplexing and even contradicting. This research adopted a multi-method approach to investigate region-specific air pollution characteristics and sources in China, results obtained using different analytical and receptor modeling methods were inter-compared for validation and interpretation. A year-round campaign was completed for comprehensive characterization of PM2.5 over four key emission regions: Beijing-Tianjin-Hebei (BTH), Yangzi River Delta (YRD), Pearl River Delta (PRD), and Sichuan Basin (SB). Atmospheric PM2.5 samples were collected from 10/2012 to 08/2013 at four regional sites, located on the diffusion paths of air masses from their corresponding megacities (i.e., Beijing, Shanghai, Guangzhou, and Chengdu). The annual average PM2.5 mass concentrations showed distinct regional difference, with the highest observed at BTH and lowest at PRD site. Nine water-soluble ions together contributed 33–41% of PM2.5 mass, with three dominant ionic species being SO4 2−, NO3 −, NH4 +, and carbonaceous particulate matter contributed 16–23% of PM2.5 mass. This implied that combustion and secondary formation were the main sources for PM2.5 in China. In addition, SO4 2−, NO3 −, NH4 +, and carbonaceous components (OC, EC) showed clear seasonal patterns with the highest concentration occurring in winter while the lowest in summer. Principal component analysis performed on aerosol data revealed that vehicular emissions, coal/biomass combustion, industry source, soil dust as well as secondary formation were the main potential sources for the ionic components of PM2.5 . The characteristic chemical species combined with back trajectory analysis indicated that BTH was heavily influenced by air masses originating from Mongolia and North China Plain regions, whereas SB suffered from both local emissions of Sichuan Basin and biomass burning via long-range transport from South Asia. Sourcing conclusions from this study will be compared, validated and interpreted with those obtained using organic molecular marker and carbon isotope analyses to be presented parts II and III of this series. Highlights: Seasonal variation of ion and OC/EC in PM2.5 over 4 regional sites was characterized. The sites were affected by local emissions and air masses via long-range transport. Main sources are from vehicular emission, coal/biomass combustion industry source.